Grænser i landskabet - Sten- og jorddiger - Kristensen, Tenna R. (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
The stone and earth banks belong to a category of archaeological evidence, which can contribute to our understanding of the cultural landscape. Often, however, they do not receive the attention they deserve. They are spread across the agricultural landscape like a fine mesh and may provide information about agricultural systems, administrative borders, and previous land ownership. Most of the stone and earth banks were erected during the reorganisation of the villages’ lands towards the end of the 18th century but may also be older. Museum Sønderjylland has worked with the stone and earth banks for many years to preserve this category of evidence – increasingly so, they are in danger of disappearing completely due to modern intensive agricultural cultivation methods. Studies in five areas of eastern Denmark have shown that 70 % of the banks shown on maps from 1884 had disappeared in 1981 (Bang 2009, 6). In this way, important pieces have been lost to the understanding of the cultural landscape. The purpose of this article is to draw attention to the fact that the still preserved banks in many cases are the last and only visible evidence of abandoned farms, villages and older field and cultivation systems. The purpose is also to investigate the extent to which the banks appearing on historical maps can be found in the archaeological excavations.